HUBUNGAN PERSEPSI IBU DENGAN IMUNISASI CAMPAK PADA BAYI USIA DI ATAS 9 BULAN DI POSYANDU MOJOWUKU SLEMPIT GRESIK - Imandra Arif Bachtiar; Chilyatiz Zahroh (Universitas Nahdlatul Ulama Surabaya, 2017)
The habitual of Some mothers living around Posyandu Mojowuku tend not to provide their babies with measles immunization because of the perception that measles immunization can cause fever in babies. The fact that they do not receive information about immunization from the health workers creates a wrong perception that brings bad effects to babies. Hence, the purpose of this study was to find out the correlation between mother’s perception and measles immunization in babies aged over 9 months. This study was cross sectional approach involved the population of all mothers having babies aged over 9 months, totaling 63 couples. The samples of research 54 respondents were chosen using Non Probability sampling and Purposive sampling technique. Questionnaire and maternal-child health booklet were used to collect the data. Analyzed using Chi-Square test with the level of significance α = 0.05. The result showed that most of the mothers (66.7%) had positive perception about measles immunization, whereas most of the babies (70.4%) received measles immunization. Moreover, the result of Chi-Square test showed that ρ = 0,000 < so that H0 was rejected illustrating that there was a correlation between mother’s perception and measles immunization in babies aged over 9 months. Mother’s perception significantly affected the coverage of measles immunization in babies. Hence, those who have negative perception about measles immunization are expected to change their opinion and perception to avoid dangers for their babies. Moreover, the health workers are also expected to promote activities of providing them with health education to increase their awareness of measles immunization.